Extra-intestinal non-typhoidal Salmonella infections in children - Lee, Way Seah; Puthucheary, S.D.; Parasakthi, N. (2000)
Extra-intestinal non-typhoidal Salmonella (NTS) infections are uncommon in developed countries but common in developing ones. The risk factors, clinical features and outcome of children admitted to the Department of Paediatrics, University of Malaya Medical Center, Kuala Lumpur from 1978 to 1998 with extra-intestinal NTS infections were reviewed. All positive cultures of NTS, blood, cerebrospinal fluid, urine, synovial, pericardial and other body secretions (except stools), were included. Of the 98 cases reviewed, 56 were boys and 42 girls. The mean age was 2.1 years (range: newborn to 14 years). Twenty-seven children were severely immunocompromised and 21 had underlying chronic medical disorders. Bacteraemia was the most commonly detected type of infection and meningitis the commonest focal infection. The overall mortality rate was 15. An immunocompromised stare or underlying chronic medical disorder was associated with increased mortality. The three serotypes most commonly isolated were S. enteritidis, S. paratyphi B and S. typhimurium. Most isolates were sensitive to antibiotics commonly used in salmonellosis.